Overview of the health care system in Hong Kong and its referential significance to mainland China. Issue 10 (October 2015) - Kong, Xiangyi; Yang, Yi; Gao, Jun; Guan, Jian; Liu, Yang; Wang, Renzhi; Xing, Bing; Li, Yongning; Ma, Wenbin
Abstract : Abstract : Hong Kong's health system was established within the framework of a perfect market‐oriented economic matrix, where there are wide‐ranging social security and medical service systems. There are many differences in the economic foundations, social systems, and ideologies between Hong Kong and mainland China, therefore, it would probably be entirely impossible to copy Hong Kong's health care system mode. However, under the framework of one country, two systems, the referential significance of relevant concepts of Hong Kong's medical service system to mainland China cannot be ignored, and merits further study.